AN ANALYSIS OF STUDENTS' ABILITY IN WRITING AN INVITATION LETTER - Moh Mahmud; Rohsita (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Writing is one of the most important skills in the English language that students must master at school, while the eleventh grade students of Madrasah Aliyah Al Amiriyyah still had problems in writing, especially in writing invitation letters, most of them were not understand well about part of invitation letter and to design their sentences. Besides they were also less vocabulary in writing invitation letter. So the aim of research is to describe student's ability in writing an invitation letter at the eleventh grade students of Madrasah Aliyah Al Amiriyyah Blokagung Banyuwangi. The method in this research is descriptive qualitative. The data was taken from the results of the researcher's observations on the learning carried out in class, especially on the invitation letter material. The results of the analysis of students' writing skills on an invitation letter are that three students are included in the sufficient category with scores obtained 64, 66, 62 and one student is included in the good category with a score of 75. This indicates that the writing ability of the eleventh grade students of MA Al Amiriyyah on an invitation letter is still low and there is a need for improvement in better writing learning methods.